Aetiology of low birth weight in a plantation population in Nuwara Eliya, Sri Lanka. - Perera, R.S (My University, 1989)
The objective of this study was to identify the aetiological factors of low birth weight in this context.For this study an up-country plantation population in Nuwara Eliya was selected.Following measures have been recommended to reduce the low birth weight incidence on up-country plantations:- Maternity leave in the two weeks penultimate to delivery should be ensured.Maternal weight gain should be monitored at ante-natal clinics to ensure a weight gain of 300g,per week or more," At risk" care should be given to mothers with a past history of low birth weight and low maternal height.Mothers in parity 1 or with an age of below 20 years or between 30-34 years should also receive special care,Spacing of births to 24 months or above should be achieved with family planning and breast feeding,Health education should be given to mothers to commence ante-natal care early in the pregnancy,preferably before 20 weeks of gestation,Regular ante-natal clinic visits should be promoted and,Better literacy should achieved through education.